Mathematical modeling of the competition between acquired immunity and cancer - Kolev, Mikhail (Zielona Góra: Uniwersytet Zielonogórski)
In this paper we propose and analyse a model of the competition between cancer and the acquired immune system. The model is a system of integro-differential bilinear equations. The role of the humoral response is analyzed. The simulations are related to the immunotherapy of tumors with antibodies.
Keywords: leukemia; acquired immunity; immunotherapy; antibodies; integro-differential equations